Reconstructing unnatural narrative structure using dramatism theory in Harold Pinter’s betrayal and Charlie Kaufman’s eternal sunshine of the spotless mind - Mohd Said, Nur Aainaa Amira (2021)
Being a part of new narratology, unnatural narratology explores the unconventional methods authors used in their literary works. Similar to natural narratology, unnatural narratology suggests multiple ways for readers to interpret and understand unnatural texts. However, instead of naturalizing the unnaturalness, unnatural narratologists acknowledge and appreciate the intricacy of such texts. Accordingly, there are three categories of unnatural narratives: unnatural storyworlds, unnatural minds, and unnatural acts of narration. In view of this concept, this study emphasizes the reconstruction of unnatural narrative structure using Kenneth Burke’s dramatism theory in Harold Pinter’s play Betrayal and Charlie Kaufman’s screenplay Eternal Sunshine of the Spotless Mind. Both texts are chosen due to their similar reverse chronological narrative which is presented as a part of an unnatural storyworld. It refers to the complex and non-realistic world depicted in the texts where the sequence of events is unfolded opposite to the temporal aspect of the real world. In other words, the reverse narrative in both texts is fundamental to their thematic values and textual structures instead of acting as a mere background setting. There are three research objectives focusing on the narratological aspects of the texts’ structure. The first objective establishes the connection between the main characters’ actions and motives with the central pentadic ratio of selected texts. Next, the second objective focuses on the reconstruction of the texts’ reverse narrative structure using pentadic ratios and five stages of the guilt-redemption cycle without altering their overall meanings and thematic values. Lastly, the third objective examines the significance of the reverse chronology technique by comparing it with the ‘natural’ reading of the texts. To achieve the first two research objectives, two components of dramatism theory are utilized in which the dramatistic pentad is used to analyze the main characters’ actions and motives whereas the guilt-redemption cycle is implemented when reconstructing the narrative structure of the texts. Lastly, the third research objective explores Monika Fludernik’s concept of ‘natural’ narratology and Alber et al.’s concept of unnatural narratology. As a result, based on the findings of the study, it is affirmed that the reverse narratives in Betrayal and Eternal Sunshine of the Spotless Mind do not only assist in upholding the major themes but also accentuate the underlying messages and overall meanings of the texts. Simultaneously, this research also posits a reading model for future studies to possibly adapt to interpret and cognize reverse and unnatural narratives in a different perspective. Notwithstanding its utilization in rhetoric studies, dramatism theory is still relevant and significant to be a part of the analytical tools for literary analyses particularly on the narrative structure of play and screenplay texts.